2020
DOI: 10.1101/2020.06.25.170688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Evolution of SARS-CoV-2 Structural Genes: Evidence of Positive Selection in Spike Glycoprotein

Abstract: AbstractSARS-CoV-2 caused a global pandemic in early 2020 and has resulted in more than 8,000,000 infections as well as 430,000 deaths in the world so far. Four structural proteins, envelope (E), membrane (M), nucleocapsid (N) and spike (S) glycoprotein, play a key role in controlling the entry into human cells and virion assembly of SARS-CoV-2. However, how these genes evolve during its human to human transmission is largely unknown. In this study, we screened and analyzed rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Despite this uniquely high fidelity of replication, a number of mutations to the SARS-CoV-2 genome have been observed throughout the present course of the COVID-19 pandemic, including in the S gene. Indeed, analysis of 3090 isolates in June 2020 found that the number of unique alleles of S was greater than the other structural genes M, N, and E, suggesting that changes in S may provide an evolutionary benefit [ 31 ]. One non-synonymous mutation of S gene in particular, an aspartic acid-to-glycine substitution at amino acid position 614 (D614G), has attracted immense attention following reports of its enrichment discovered by epidemiological surveillance [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this uniquely high fidelity of replication, a number of mutations to the SARS-CoV-2 genome have been observed throughout the present course of the COVID-19 pandemic, including in the S gene. Indeed, analysis of 3090 isolates in June 2020 found that the number of unique alleles of S was greater than the other structural genes M, N, and E, suggesting that changes in S may provide an evolutionary benefit [ 31 ]. One non-synonymous mutation of S gene in particular, an aspartic acid-to-glycine substitution at amino acid position 614 (D614G), has attracted immense attention following reports of its enrichment discovered by epidemiological surveillance [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another group observed a similar trend, although not statistically significant in their dataset [ 40 ]. Moreover, computational models of evolutionary dynamics suggest that D614G is under strong selective pressure [ 31 ]. Further, quantitative estimates of the basic reproductive number R 0 from infection incidence data suggest that viruses bearing S(G614) are 31% more transmissible than D614, although this analysis did not consider the effect of concomitant changes at other loci in the circulating viral strains [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study also reported that of 250 high coverage complete genome hCoV-19/Malaysia strains deposited in the GISAID database, 114 of the virus strains harboured D614G mutations in Spike protein ( Table 3 ). Altogether, these results suggest the SARS-CoV-2 Malaysia isolate was subjected to intense positive selection pressure [29] and a persistent D614G mutation identified may be responsible for the quick spread of SARS-CoV-2 in Malaysia.
Fig.
…”
Section: Resultsmentioning
confidence: 87%
“…3 ). Therefore, suggesting Pahang/IIUM91 was not correlated to Sivagangga cluster, which originated from India [29] .
Fig.
…”
Section: Resultsmentioning
confidence: 92%
“…Further evolution of these spike proteins could enhance binding to human ACE2, enhancing transmission, infection rate, virulence, while exacerbating symptoms. Specific interest has focused on codon 614 of an especially glycosylated region of the viral spike protein, where positive natural selection has been confirmed for the D614G variant [7,12,19].…”
Section: Introductionmentioning
confidence: 99%